การประมาณค่าอัตรามรณะของผู้สูงอายุไทยโดยใช้ตัวแบบคานนิสโต ตัวแบบเมคแฮม ตัวแบบเวอร์สเมคแฮม และทฤษฎีค่าสุดขีด - สยุมภู สายชลพิทักษ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
To estimate and compare the estimation of Thai elderly mortality rates by using 4 estimated models: 1) Kannisto model, 2) Makeham model, 3) Inverse-Makeham model, and 4) Extreme-value theory. The estimated mortality rates from 3 models were compared with mortality rates from civil registration data using mean absolute percent error (MAPE). The Extreme-value theory is used to estimate mortality rate in the high level ages. Then the estimated mortality rates from research were compared with the mortality rates from Thai Mortality Ordinary Table 1997 (TMO97) and the mortality rates from Thai Pension Table 2009. Data used in the study are the number of population and the number of death by age and sex of the year 2003-2008 from the Ministry of Interior and the Ministry of Public Health respectively. The study found that the Inverse-Makeham model gives the lowest MAPE value for males in the age rage 60-85 years and females’ age 60-83 years. Combine the estimated mortality rates from Inverse-Makeham Model and Extreme-Value Theory then compare to the mortality rates from TMO97 found that there is very similar in age range 60-82 years and 60-85 years for males and females, respectively. Moreover, the estimated mortality rates are near the mortality rates from Thai Pension Table 2009 in age range 60-92 years and 60-93 years for males and females, respectively.